(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
This paper is concerning with essential degree of approximation using regular neural networks and how a multivariate function in spaces for can be approximated using a forward regular neural network. So, we can have the essential approximation ability of a multivariate function in spaces for using regular FFN.